Transforming Educational Leadership: Efforts of the Principal in Enhancing Staff Professionalism at Raudlatul Athfal An-Nawa 3 Cirebon - Wahyono, Wahyono; Pramesti, Olivia (Rausyan Fikri Journal of Islamic Studies, 2025)
Leadership of the Principal as Supervisor in Improving the Professionality of Staff in Ra An-Nawaa 3 City of Cirebon. Principal is the most important factor in an educational institution, namely the school, from several principal tasks, namely supervising, managing, and controlling. The principal's job is to maintain the quality of the school so that it can compete and become a reference for finding new students. The task of the principal also requires several competent educational staff in the field of controlling school quality. Supervision is needed to increase the quality and performance of staff through supervision of schools in order to determine the ability of staff to develop school quality. This study uses the theory of supervision consisting of GROWME Goal, Reality, Option, Way forward, Monitoring, and Evaluation. To see staff performance using staff theory with indicators of promotion, further study, staff observations when carrying out work, individual meetings, visits between institutions. This study aims to describe the role of the principal as a supervisor in improving staff professionalism at RA An-Nawaa 3, Cirebon City. This study uses a qualitative descriptive method to develop research and the results of this study are to see that the staff's performance is good and can be developed again. The results of this study show that the implementation of supervisors in improving staff professionalism at RA An-Nawaa 3 carried out by the principal in developing staff professionalism has two ways of implementation, namely using meeting media and field discovery media in every aspect of staff professionalism.